Short Is Beautiful: Dimensionality and Measurement Invariance in Two Length of the Basic Psychological Need Satisfaction at Work Scale - Eriksson, Mårten; Boman, Eva (Frontiers in Psychology, 2018)
Self-determination theory proposes that all humans have three intrinsic psychological needs: the needs for autonomy, competence and relatedness. These needs take different forms in different areas of life. The present study examines the psychometric properties of a Swedish version of the Basic Psychological Need Satisfaction at Work (BPNS-W) scale. The fit of 10 factor structures previously suggested for related versions of the scale were compared. Cross-sectional data from 1,200 participants were examined in a confirmatory factor analysis (CFA) framework. Both the original 21-item version and a reduced, 12-item version of the BPNS-W were examined. The General Health Questionnaire was used for validation. The results supported a three-factor solution with correlated error variances for the reversed items. Invariance testing of the long and short scales gave best support to the short scale, for which partial scalar invariance was achieved. The external validity of the short scale was supported by a hierarchical regression analysis in which each need made a unique contribution in predicting psychological well-being. In conclusion, the results corroborate a three-factor structure of BPNS-W. Although not perfect the short scale should, it is argued, be preferred over the long version. Directions for the future development of the scale are discussed.